After-Effects of Intermittent Theta-Burst Stimulation Are Differentially and Phase-Dependently Suppressed by α- and β-Frequency Transcranial Alternating Current Stimulation - Ogata, Katsuya; Nakazono, Hisato; Ikeda, Takuro; Oka, Shin-ichiro; Goto, Yoshinobu; Tobimatsu, Shozo (Frontiers in Human Neuroscience, 2021)
Intermittent theta-burst stimulation (iTBS) using transcranial magnetic stimulation (TMS) is known to produce excitatory after-effects over the primary motor cortex (M1). Recently, transcranial alternating current stimulation (tACS) at 10 Hz (α) and 20 Hz (β) have been shown to modulate M1 excitability in a phase-dependent manner. Therefore, we hypothesized that tACS would modulate the after-effects of iTBS depending on the stimulation frequency and phase. To test our hypothesis, we examined the effects of α- and β-tACS on iTBS using motor evoked potentials (MEPs). Eighteen and thirteen healthy participants were recruited for α and β tACS conditions, respectively. tACS electrodes were attached over the left M1 and Pz. iTBS over left M1 was performed concurrently with tACS. The first pulse of the triple-pulse burst of iTBS was controlled to match the peak (90°) or trough (270°) phase of the tACS. A sham tACS condition was used as a control in which iTBS was administered without tACS. Thus, each participant was tested in three conditions: the peak and trough of the tACS phases and sham tACS. As a result, MEPs were enhanced after iTBS without tACS (sham condition), as observed in previous studies. α-tACS suppressed iTBS effects at the peak phase but not at the trough phase, while β-tACS suppressed the effects at both phases. Thus, although both types of tACS inhibited the facilitatory effects of iTBS, only α-tACS did so in a phase-dependent manner. Phase-dependent inhibition by α-tACS is analogous to our previous finding in which α-tACS inhibited MEPs online at the peak condition. Conversely, β-tACS reduced the effects of iTBS irrespective of its phase. The coupling of brain oscillations and tACS rhythms is considered important in the generation of spike-timing-dependent plasticity. Additionally, the coupling of θ and γ oscillations is assumed to be important for iTBS induction through long-term potentiation (LTP). Therefore, excessive coupling between β oscillations induced by tACS and γ or θ oscillations induced by iTBS might disturb the coupling of θ and γ oscillations during iTBS. To conclude, the action of iTBS is differentially modulated by neuronal oscillations depending on whether α- or β-tACS is applied.